Bactercline®-coated implants: Clinical results up to 1 year after loading from a controlled clinical trial - Francesco Carinci; Emma Grecchi; Carlo Alberto Bignozzi; Giovanna Murmura; Adriano Piattelli; Antonio Scarano (Wolters Kluwer Medknow Publications, 2012)
Background: Titanium dioxide exists in three different crystal lattices, anatase, rutile, and brookite. Anatase coating releases, under ultraviolet (UV) irradiation, free radicals such as ·OH, O 2 - , HO 2 - , and H2 O2 . This potent oxidizing power characteristically results in the lysis of bacteria and other organic substances. The purpose of this study was to evaluate the bone response to implants made of titanium alloy or coated with a new combination of anatase and Bactercline® product. Materials and Methods: In the period between July 2009 and June 2010, 26 patients (10 females and 16 males; median age 51 ± 11 years, min. 27 years, max. 72 years) were operated and 62 implants were inserted. Lost fixtures and peri-implant bone resorption were considered as predictors of clinical outcomes. Pearson χ2 -test was used. Prosthesis and implant failures, any complications after loading, and peri-implant marginal bone-level changes were assessed by a masked assessor. All patients were followed up to 1 year after loading. Results: No implant was lost. Average bone resorption around implant was 0.33 mm (both for 25 standard and 37 Bactercline-coated implants), and thus no statistical difference was detected. Conclusion: These results shown that no adverse effects on osseo-integration were present.